Design and fabrication of three axis mechanism with AC servo motor in application of personal computer numerical control - Lim, Liang Heong (2007)
This project was carried out to develop the accuracy and efficiency of the three axis mechanism with AC servomotor in application of personal computer numerical control. For running the incremental forming rig test is the main objective of this project. This three axis mechanism prototyping had been involved designed,analyzed, simulation approach, fabrication and assemble work. The structure part is one most important design part to minimize the vibration and friction. Extension simulations were performed to consider the failure analysis of the structure. The table structure found that it is strong enough to support the force and load which cause it bends about 3.11 mm and maximum stress applied is 5.11 MPa. The ultimate tensile strength is far higher than maximum stress applied. This three axis mechanism machine is successful develop. High technology electrical devices and good control system used to increase the accuracy and efficiency of the product.